1993
DOI: 10.1111/j.1438-8677.1993.tb00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and Glutamate Transport in Cyanophora paradoxa

Abstract: The present investigation showed that isolated cyanelles from Cyanophora paradoxa selectively enriched glutamine from the external medium, whereas glutamate poorly penetrated into these organelles. Glutamine uptake proceeded in two phases, presumably involving a low and a high affinity system. The uptake of glutamine was significantly enhanced by 2‐oxoglutarate and light. Inhibitor experiments indicated that glutamine and 2‐oxoglutarate were converted to glutamate by a ferredoxin‐dependent glutamate synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The DiTs [ 39 ] are present only in green algae, plants, and bacteria (that is, not in red algae). Whereas genomic data for glaucophytes are not yet available, transport experiments using isolated Cyanophora cyanelles showed that this glaucophyte uses a transport system for glutamine and 2-oxoglutarate that is distinct from green plant DiTs [ 40 ]. Taken together, these data indicate that ' Chlamydia -like' dicarboxylate translocators have likely been lost from red algae and glaucophytes.…”
Section: Resultsmentioning
confidence: 99%
“…The DiTs [ 39 ] are present only in green algae, plants, and bacteria (that is, not in red algae). Whereas genomic data for glaucophytes are not yet available, transport experiments using isolated Cyanophora cyanelles showed that this glaucophyte uses a transport system for glutamine and 2-oxoglutarate that is distinct from green plant DiTs [ 40 ]. Taken together, these data indicate that ' Chlamydia -like' dicarboxylate translocators have likely been lost from red algae and glaucophytes.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic surveys indicate that the dicarboxylate transporters are of chlamydial origin, reinforcing the hypothesis on the importance these intracellular parasites had in the establishment of endosymbiosis (Tyra et al, 2007 ). In isolated C. paradoxa muroplasts, transport activities for glutamine and 2-oxoglutarate could be measured (Kloos et al, 1993 ). In uptake experiments with isolated cyanelles by silicone oil filtering it could be shown that glutamate poorly penetrated into cyanelles, whereas glutamine was enriched in the plastid fraction by 1.7 fold within 10 min.…”
Section: Other Transportersmentioning
confidence: 99%
“…In uptake experiments with isolated cyanelles by silicone oil filtering it could be shown that glutamate poorly penetrated into cyanelles, whereas glutamine was enriched in the plastid fraction by 1.7 fold within 10 min. Glutamine uptake proceeded in two phases and was stimulated by 2-oxoglutarate (Kloos et al, 1993 ). Ammonia formed by nitrite reduction inside the cyanelles is incorporated by GS into glutamine and then exported jointly with oxoglutarate (Kloos et al, 1993 ).…”
Section: Other Transportersmentioning
confidence: 99%
“…Cyanelles have recently been shown to perform photorespiration (Betsche et al, 1992), thus transport of glyoxylate and/or other compounds is to be expected. Cyanelles transport amino acids by specific carriers which is described in the accompanying paper (Kloos et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The previous results (Schlichting et ai.,1990) indicated that cyanelles possess neither a malate/oxaloacetate carrier nor an ATP/ ADPtranslocator. This communication describes properties of a phosphate translocator and a glucose carrier in the cytoplasmic membrane of cyanelles whereas the accompanying paper (Kloos et al, 1993) characterizes the exchange of nitrogenous compounds from and to cyanelles.…”
mentioning
confidence: 99%